PEMAKNAAN NORMA KONSTITUSI DALAM PENGUATAN DEWAN PERWAKILAN DAERAH DALAM RULE MAKING FUNCTION - Adhitya Widya Kartika (Arena Hukum, 2021)
AbstractThe existence of the House of Representatives (DPD) in including regional inputs in the form of norms has experienced polemics. These polemics include the decisions of the State Administrative Court (PTUN), the Supreme Court (MA), and the Constitutional Court (MK) that are out of sync with one another. This decision has the impact of legal dualism which results in confusion for the General Election Commission (KPU) to carry out its functions and even disharmony between legal norms. This normative research aims to determine the existence of a basis to support the DPD in order to reduce conflicts of interest. As a result, the KPU, when viewed from the normative aspect, the Constitutional Court is the sole interpreter of the constitution because of the authority granted by the constitution in Article 24 C. If so, then the KPU does not have to worry about implementing the Constitutional Court's decision because it is constitutional. That is, the KPU carrying out the Constitutional Court's Decision means maintaining the dignity of the DPR so that the aspirations carried out truly represent the needs of the region without worrying about conflicts of interest because they have as administrators of political parties.AbstrakEksistensi Dewan Perwakilan Daerah (DPD) dalam memasukkan aspirasi daerah dalam bentuk norma mengalami polemik. Polemik ini diantaranya adanya Putusan Pengadilan Tata Usaha Negara (PTUN), Mahkamah Agung (MA), serta Mahkamah Konstitusi (MK) yang tidak sinkron antara satu dengan lainnya. Putusan tersebut membawa dampak adanya dualisme hukum yang berkakibat pada kebingungan Komisi Pemilihan Umum (KPU) untuk menjalankan fungsinya bahkan terjadi inkonsistensi norma sehingga terjadi ketidak-harmonisan antar norma hukum. Penelitian normatif bertujuan mengetahui eksistensi penafsiran konstitusi untuk penguatan DPD demi mengurangi konflik kepentingan. Hasilnya, KPU, apabila dilihat dari aspek penormaan, MK merupakan penafsir tunggal konstitusi karena kewenangannya yang diberikan oleh konstitusi pada Pasal 24 C karena kedudukan norma dasar maka Putusan PTUN menjadi inkonstitusional. Jika demikian maka KPU tidak perlu kawatir dalam menjalankan Putusan MK karena konstitusional. Artinya, KPU apabila menjalankan Putusan MK berarti mempertahankan marwah DPR sehingga aspirasi yang diusung benar-benar mewakili kebutuhan daerah tanpa khawatir adanya konflik kepentingan karena menjabat sebagai pengurus partai politik.Â